BIOPHYSICS ENVIRONMENTAL CONDITIONS OF SWAMP BUFFALO Bubalus bubalis PAMPANGAN IN DISTRICT RAMBUTAN SOUTH SUMATERA - Yuanita Windusari; Erwin Nofyan; Mustafa Kamal; Laila Hanum; Rahmat Pratama (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Swamp buffalo (Bubalus bubalis) is a germ plasm specific of Pampangan and endemic in South Sumatera with low productivity and limited distribution. The aims of this study was to obtain information regarding biophysical conditions in the central areas of swamp buffalo in South Sumatera. The method used is purposive sampling method. Data collected in the form of quantitative and qualitative. Primary data were obtained through direct observation, interviews breeders selected as respondents while secondary data obtained from various related. The data obtained are presented descriptively and data tabulation. Productivity of swamp buffalo Pampangan can be increased by managing and maintaining habitat conditions although traditional maintenance. The results of observations of the biophysical condition of swamp buffalo (B. bubalis) Pampangan showed that habitat of swamp buffalo Pampangan consists of dominated by lowland swamp area is overgrown with shrubs and grass. The conclution of the research are productivity and population of swamp buffalo (B. bubalis) pampangan as specific plasma nutfah of South Sumatra can be improved by studying the characteristics and preferred habitat of the buffalo, although developed in a traditional farms but is good enough and so need to be developed, grass is most preferred by swamp buffalo Pampangan derived from ‘Kumpai’ grass group, and ‘Kasur’grass and ‘Kumpai’ grass is the dominant grass type found in habitat swamp buffalo Pampangan.